Canalis Sinuosus Damage after Immediate Dental Implant Placement in the Esthetic Zone - Roman Volberg; Oleg Mordanov (Hindawi Limited, 2019)
Dental implant failure in the anterior maxilla can be caused by the range of the features. One of them is neighboring neurovascular structure damage, such as the canalis sinuosus (CS), that carries the superior anterior alveolar nerve. The aim of the report is to demonstrate clinical symptomatology and radiographic signs of CS damage in a 45-year-old female patient who underwent upper left lateral incisor extraction and immediate implant placement and implant removal in 16 days secondary to pain and paresthesia in the maxillary left region.